Aquifer simulation model in Tioman Island - Daulay, Hasan; Abd. Rahman, Norhan; Mohd. Nasir, Kamarul Azlan (Faculty of Civil Engineering, UTM, 2000)
Tioman Island which is situated in the southeast of Pahang State is one of small islands in Malaysia that has been promoted as a tourism destination. Based on previous study, the island requires more than 2000 m3/day of water for domestic and tourism industry consumption, and the demand is expected to rise due to the increases in population and tourism activities. Study on groundwater of Tekek aquifer indicates a good potential for water resource to meet the demand of the future water-needs in Tioman Island. An intensive study is being carried out to investigate the quantity of water resources in the island. For predicting the amount of groundwater potential that can be extracted, ASM (Aquifer Simulation Model) is used. The paper present the finding of the amount of the groundwater potential that can be extracted in Tekek, Tioman Island.